Website Design as a Promotional Media for Red Orchid Hotel Semarang - Rahma Fitri Surayah Putri; Jumi - Jumi; Budi - Prasetya (Politeknik Negeri Semarang, 2022)
There are 75 three-star hotels and 94 two-star hotels overall in Semarang. This number demonstrates the severe competition in the hospitality industry of Semarang and highlights the importance of website design as a marketing tool in the present digital era. Red Orchid has delayed creating a website since they do not completely comprehend how important it is as a promotional tool. The waterfall model was utilized in the creation of this website. The waterfall method is an easy-to-understand approach to project management, and it includes system engineering, analysis, design, programming, testing, and maintenance. The ability to identify design errors throughout the analysis and design phases is an additional advantage of this method for developers. The Red Orchid Hotel Semarang's market reach has expanded as a result of the website's design. Visitors can save both time and money by using the website, which lets them look for information that has been updated. With the use of this website, the hotel may spend less on marketing and more time working efficiently. The Red Orchid Hotel Semarang's website was designed using the CMS WordPress and in accordance with the hotel's standards procedure in order to increase the hotel's exposure online. The design of a user-friendly and attractive website for the Red Orchid Hotel Semarang has the potential to be an efficient promotional medium and to expand the hotel's overall market reach